Er nokkur í kórónafötum hér inni? - Einar Már Guðmundsson 1954- (Mal og menning, 2020)
Er nokkur í kórónafötum hér inni? was the first book of poems by Icelandic award winning author Einar Már Guðmundsson. From the start it was obvious that here was a clearly distinctive voice with an urgent message. This book contains his first three books of poems published in 1980 and 1981.